Luminescent push-pull triphenylamine-based molecules end-capped with various electron-withdrawing groups: Synthesis and properties. (December 2022) - Balakirev, Dmitry O.; Solodukhin, Alexander N.; Peregudova, Svetlana M.; Svidchenko, Evgenia A.; Surin, Nikolay M.; Fedorov, Yuriy V.; Ponomarenko, Sergey A.; Luponosov, Yuriy N.
Abstract: Organic luminescent materials are widely used in various electronic and optoelectronic devices upon growing demands of science and technology. Enhancement of spectral-luminescence characteristics for such materials and in depth understanding of "structure-property" relationships remain challenging tasks. Herein, we report on synthesis and comprehensive investigation of the series of novel luminescent push-pull molecules with triphenylamine unit as an electron donor block and thiophene as a π-spacer, which end-capped with various types of electron-withdrawing groups (EWGs), which are commonly used for the molecular design of various functional materials in organic electronics. The results allowed us to evaluate the impact of EWG type used on the target materials characteristics. Phenyl-substituted EWGs were found to be more suitable for the design of highly thermally and electrochemically stable materials with relatively high melting temperatures and melting enthalpies. Depending on the EWG nature luminescence maxima of the luminophores demonstrated significant variability, e.g. from 509 nm to 750 nm, while the photoluminescence quantum yield (PLQY) values laid in the range of 1–89%. All luminophores showed good compatibility with a polystyrene (PS) matrix, in which PLQYs were generally higher (up to 25-fold enhancement) compared to the corresponding solutions or polycrystalline films. The changes of spectral characteristics observed for these luminophores were well described using basic relations of the semi-empirical theory of solvatochromism. Based on lifetime of excited states measurements, it was shown that the excited state non-radiative deactivation constants values the major contributors to PLQY values in THF solutions, while increase of the PLQY values in PS films can be associated with decrease of the probability of non-radiative deactivation of the excited states. Graphical abstract: Image 1 Highlights: Synthesis and comprehensive investigation of luminophores with various EWG were reported. Impact of the EWG type on optical, photophysical and thermal properties was evaluated. Some luminophores have high PLQY in films and polystyrene matrix. Ph-based EWG are suitable to design materials with high thermal/electrochemical stability.